2009
DOI: 10.4103/0253-7176.53312
|View full text |Cite
|
Sign up to set email alerts
|

Role of Family and Peers in Initiation and Continuation of Substance Use

Abstract: Aims:To assess the impact of family and peers on both initiation and continuation of substance use among eighth, ninth and tenth grade adolescent high school students.Design:Population based cross-sectional study.Setting:Two high schools of West Bengal, India.Participants:416 students in class VIII, IX, and X in two schools.Interventions:None.Measurements:Substance use: initiation, sources, reasons for continuation. Then proportions and chi-square test was used for statistical analysis.Materials and Methods:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
(13 reference statements)
3
11
0
Order By: Relevance
“…Thinking that the majority of peers use cannabis was also associated with a stronger intention to use cannabis. This finding supports previous research that showed that the perception of the amount to which peers use cannabis increases the frequency of one's own actual cannabis use and intention to use cannabis (D'Amico & McCarthy, 2006;Nolan et al, 2008;Tsering & Pal, 2009). The scores on the middle of the scale indicated that there are subgroups who think that the majority of their peers use cannabis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thinking that the majority of peers use cannabis was also associated with a stronger intention to use cannabis. This finding supports previous research that showed that the perception of the amount to which peers use cannabis increases the frequency of one's own actual cannabis use and intention to use cannabis (D'Amico & McCarthy, 2006;Nolan et al, 2008;Tsering & Pal, 2009). The scores on the middle of the scale indicated that there are subgroups who think that the majority of their peers use cannabis.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies already showed that adolescents tend to overestimate the extent to which peers use cannabis (Kilmer et al, 2015;Van Laar & Ooyen-Houbem 2016). The most plausible explanation for the relation between the descriptive norm and cannabis use is that adolescents tend to conform to the behaviour of the majority (Nolan et al, 2008;Tsering & Pal, 2009). Correcting the norm, or denormalisation, among subgroups that overestimate the extent to which peers use cannabis could prevent adolescents from conforming their behaviour to a misperception about the amount of cannabis used by their peers.…”
Section: Discussionmentioning
confidence: 99%
“…These results therefore indicated a strong family influence to drug use and abuse among secondary school students. These findings corroborate the findings of Tsering and Pal (2009) who found out that a drug usage was associated with one or more family members especially fathers using drugs. Similarly, Coombs (2002) showed that abstainers' parents had firmer standards regarding curfew, television, schoolwork, use of alcohol and other drugs.…”
Section: Table2 Influence Of Family On Drug Abusesupporting
confidence: 91%
“…11 In the study of Tsering it was noted that influence of peer groups (urban= 61.5% and rural= 69.3%) had been seen to be the most important source of initiating substance use but the likelihood of family member using any substance also influenced initiation of smoking by young children. 15 Livaudais have reported that having friends who were smokers at baseline was associated with eventually becoming a smoker among Latino adolescents in the United States. 16.…”
Section: Discussionmentioning
confidence: 99%